2020
DOI: 10.1021/acs.jced.0c00085
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Hexavalent Chromium from Aqueous Solution by a Chitosan/Bentonite Composite: Isotherm, Kinetics, and Thermodynamics Studies

Abstract: In this work, the chitosan/bentonite composite was favorably prepared and further used for Cr­(VI) removal from aqueous solutions via a batch adsorption process. The characteristics of the chitosan/bentonite composite were determined by using scanning electron microscopy, Brunner–Emmet–Teller measurement, Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction, and the results reveal the evidence of the interaction between functional groups of chitosan with bentonite, which is helpful for the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 77 publications
4
36
0
1
Order By: Relevance
“…The current study revealed that the mechanism of Mn(II) ions adsorption not only depends on the number of functional sites in the applied adsorbent but also on the changing in the pH value as illustrated in Scheme (1). The removal of Mn(II) ions was small at low pH values (pH < 5) then it increased slowly until it reached maximum at higher pH values (ca.…”
Section: Mechanism Of Mn(ii) Ions Adsorption On the G Clay And Its Namentioning
confidence: 71%
See 1 more Smart Citation
“…The current study revealed that the mechanism of Mn(II) ions adsorption not only depends on the number of functional sites in the applied adsorbent but also on the changing in the pH value as illustrated in Scheme (1). The removal of Mn(II) ions was small at low pH values (pH < 5) then it increased slowly until it reached maximum at higher pH values (ca.…”
Section: Mechanism Of Mn(ii) Ions Adsorption On the G Clay And Its Namentioning
confidence: 71%
“…Heavy metals are considered one of the main sources of industrial wastewater pollution, which seriously menace the human health and the biological environment. It is necessary to remove the inorganic pollutants from wastewater before being discharged into the environment due to their high stability and non-degradable nature (1,2). Although some heavy metals such as manganese, copper, iron, and zinc are essential for human health under particular concentrations, but above these concentrations they become toxic and cause various health problems (3).…”
Section: -Introductionmentioning
confidence: 99%
“…The pseudo-second-order kinetic models justify the adsorption of ions on the surface of the adsorbent through chemical adsorption (chemisorption) . This model, as described by Ho and Mckay, is represented by eq …”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamics: Effect of Temperature on Adsorption. The three main thermodynamic parameters such as change in free energy (ΔG), enthalpy (ΔH), and entropy (ΔS) were determined at a temperature range from 293 to 323 K. The thermodynamic parameters were evaluated by thermodynamic van't Hoff eqs 11 and 12 39…”
Section: Resultsmentioning
confidence: 99%
“…The three main thermodynamic parameters such as change in free energy (Δ G ), enthalpy (Δ H ), and entropy (Δ S ) were determined at a temperature range from 293 to 323 K. The thermodynamic parameters were evaluated by thermodynamic van’t Hoff eqs and where K L is the equilibrium constant obtained from the proportion of adsorbate on the polymer ( Q e ) to that of the adsorbate in solution ( C e ) at equilibrium from the Langmuir model (L/g).…”
Section: Resultsmentioning
confidence: 99%